Chronic Atopic Dermatitis in Adults : A Family Medicine Approach to Psychosocial Factors and Holistic Management - Andarini, Sri; Hevy Purwaningtyas, Nuretha; Fakhrizah Wildani , Safira (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin condition often exacerbated by psychosocial stressors, significantly impacting patients' quality of life. This case highlights the intricate relationship between psychological burden and AD pathogenesis, emphasizing the crucial role of a holistic family medicine approach in its comprehensive management. We present the case of a 54-year-old male, a motivational trainer, who presented with recurrent pruritic erythematous plaques on both ankles, consistent with chronic atopic dermatitis. His symptoms were significantly aggravated by psychological stress stemming from a substantial decline in work engagements and income during the recent pandemic, which also restricted his stress-coping hobbies. Clinical evaluation, guided by Hanifin Rajka criteria, confirmed the diagnosis of atopic dermatitis, with psychological stress identified as a key exacerbating factor through neuro-immuno-cutaneous mechanisms. A comprehensive family medicine intervention was employed, integrating pharmacological management with topical corticosteroids, non-pharmacological strategies like skin barrier optimization, and extensive psychosocial counseling. The patient's functional family dynamics, as assessed by a high Family APGAR score, supported the feasibility of a multi-faceted approach, addressing both physical symptoms and underlying stressors. This case underscores the necessity of a biopsychosocial model in managing chronic conditions like atopic dermatitis. A holistic family medicine perspective, incorporating patient education, stress management, and collaborative care, is vital for achieving optimal outcomes and improving patient well-being.